Tom Mueller: Extra virginity: The Sublime and Scandalous World of Olive Oil - Nowak, Zachary (Petits Propos Culinaires, 2012)
Tom Mueller: Extra virginity: The Sublime and Scandalous World of Olive Oil: Atlantic Books, 2012, 288pp., hardback, £18.99.